Describing undiscovered insect diversity: an introduction to collected papers describing 150 new taxa - Zhang, Zhi-Qiang (Zootaxa, 2012)
The number of species on earth is estimated to be 8.7 million, with 87% of them to be discovered and described (Mora et al. 2011). The total of 8.7 million seems to be an underestimate, because for Animalia alone, over 1.5 million species have been described (Zhang 2011b). The most successful group, the Insecta, accounts for almost two-thirds of all animals.